The Effect of Use Learning Media on the Economics Outcomes Learning in Tenth Grade Students of Kalam Kudus Christian School Pematangsiantar During the Pandemic Period - Susy Alestriani Sibagariang; Holmes Rajagukguk (Jurnal Mantik, 2021)
This study aims to reveal The Effect of Use Learning Media on the Economics Outcomes Learning in Tenth Grade of Students Kalam Kudus Christian School Pematangsiantar During the Pandemic Period. The method used in this research is the experimental method. The research subjects were students of class X5 as an experimental class consisting of 50 students and class X2 as a control class consisting of 50 students. The instrument used is test results. Learning outcome tests are used to measure student learning outcomes. In testing the hypothesis the statistical test "t" is used. The results of the calculation are obtained tcount > ttabel with a =0,05 dk= (n1+n2-2) = 50+50-2 = 98 is (3,37 > 1,99 thus H0 is rejected and H1 accepted. In other words, there is a significant influence between learning using visual media on student learning outcomes in economic lessons of tenth grade students of Kalam Kudus Christian Senior High School during the Pandemic period and there is a significant difference between learning using visual media and learning without using media on the learning outcomes of students during the Pandemic Period.